PLA influence on China's national security policy-making - Saunders, Phillip C.; Scobell, Andrew (Stanford University Press, 2015)
PLA is a major player in Beijing politics. Long gone is the "military communism" in which party and army were intertwined. The PLA is one bureaucratic voice among several and usually overridden by the Ministry of Foreign Affairs. The Politburo has two PLA generals among its 25 members; the elite, seven-man Standing Committee has none. China's president and party chief claims he represents the PLA by virtue of heading the Central Military Commission.